2021
DOI: 10.1002/adma.202101155
|View full text |Cite
|
Sign up to set email alerts
|

Acidity‐Activatable Dynamic Nanoparticles Boosting Ferroptotic Cell Death for Immunotherapy of Cancer

Abstract: Immunotherapy shows promising therapeutic potential for long‐term tumor regression. However, current cancer immunotherapy displays a low response rate due to insufficient immunogenicity of the tumor cells. To address these challenges, herein, intracellular‐acidity‐activatable dynamic nanoparticles for eliciting immunogenicity by inducing ferroptosis of the tumor cells are engineered. The nanoparticles are engineered by integrating an ionizable block copolymer and acid‐liable phenylboronate ester (PBE) dynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
119
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(130 citation statements)
references
References 38 publications
(17 reference statements)
1
119
0
Order By: Relevance
“…More importantly, based on their intrinsic connections of O 2 and ROS, a combination of PDT and ferroptosis will achieve a synergistic effect to initiate strong immune response. In addition, PDT can activate T lymphocytes to release IFN-γ, which will facilitate the ferroptosis-related lipid peroxidation to further improve the ICD effect 177 - 180 . Therefore, novel nanoplatforms developed by the rational integration of PDT, ferroptosis, and immunotherapy have attracted much attention for cancer treatment 180 .…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, based on their intrinsic connections of O 2 and ROS, a combination of PDT and ferroptosis will achieve a synergistic effect to initiate strong immune response. In addition, PDT can activate T lymphocytes to release IFN-γ, which will facilitate the ferroptosis-related lipid peroxidation to further improve the ICD effect 177 - 180 . Therefore, novel nanoplatforms developed by the rational integration of PDT, ferroptosis, and immunotherapy have attracted much attention for cancer treatment 180 .…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…In addition, PDT can activate T lymphocytes to release IFN-γ, which will facilitate the ferroptosis-related lipid peroxidation to further improve the ICD effect 177 - 180 . Therefore, novel nanoplatforms developed by the rational integration of PDT, ferroptosis, and immunotherapy have attracted much attention for cancer treatment 180 . Finally, in-depth exploration of the relationship between PDT and cancer immunotherapy is still needed, and more advanced nanomedicines will boost the effectiveness and safety of combinational cancer immunotherapy 181 .…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Song et al developed acidity-activatable dynamic nanoparticles encapsulating RSL-3 to target GPX4, unveiling a strategy for ferroptosis-inducing tumor specific delivery. This nanoparticle approach acts to potentiate immunotherapy by recruiting tumor-infiltrating T lymphocytes for interferon gamma (IFNγ) secretion [57]. Hou et al demonstrated that metformin induces TNBC cell ferroptosis via an upregulation of miR-324-3p, by which GPX4 expression is inhibited by targeting its 3 UTR [58].…”
Section: Inducing Ferroptosis By Inhibiting Antioxidant Defensementioning
confidence: 99%
“… Lung metastasis of 4T1 breast tumors The combination of nanoparticle-induced ferroptosis and blockade of programmed death ligand 1 efficiently inhibits growth of B16-F10 melanoma tumor and lung metastasis of 4T1 breast tumors, suggesting the promising potential of ferroptosis induction for promoting cancer immunotherapy. [ 90 ] Zero-valent-iron nanoparticle (ZVI-NP) ZVI-NP caused mitochondria dysfunction, intracellular oxidative stress, and lipid peroxidation, leading to ferroptotic death of lung cancer cells. Degradation of NRF2 by GSK3/β-TrCP through AMPK/mTOR activation was enhanced in such cancer-specific ferroptosis.…”
Section: The Role Of Ferroptosis In Lung Cancermentioning
confidence: 99%